Histopathologic infiltration pattern predicts metastasis and progression better than pT-stage and grade in well-differentiated pancreatic neuroendocrine tumors: A proposal for an infiltration-based morphologic grading system - Taşkın, Orhun; Reid, Michelle; Bağcı Çulçi, Pelin; Balcı, Serdar; Armutlu, Ayşe; Demirtaş, Deniz; Pehlivanoğlu, Burçin; Saka, Burcu; Memiş, Bahar; Bozkurtlar, Emine; Leblebici, Can Berk; Corobea, Adelina Birceanu; et al. (Springer Nature, 2021)
[Abstract Not Available]
Keywords: Infiltration Pattern Predicts; pT-Stage; Grade in Well-Differentiated Pancreatic Neuroendocrine Tumors